Safety Monitoring System in Minimg Environment Using Iot. Issue 1 (January 2021) - Kavitha, D.; Chinnasamy, A.; Devi, A. Sangeerani; Shali, A.
Abstract: The average mine worker is exposed to the harsh underground environment which can sometimes cause an injury or loss of life. The older methods of mine condition monitoring involved using a person to go down and report back. This method is however dangerous as the person who is monitoring a specific hazard could be harmed by that hazard. This standard can be reinforced through the implementation of modern technology which is central to the non-invasive mine safety system with wireless sensor networks to obtain the best possible result.